Answer:
[tex]81/4[/tex]
Step-by-step explanation:
From the question we are told that
The equation is given by
[tex]x^2+9x+7=0[/tex]
Generally completing the square method is mathematically solved
[tex]x^2+9x+7=0[/tex]
[tex]x^2+9x=-7[/tex]
[tex]x^2+2(\frac{9}{2})x =-7[/tex]
[tex]x^2+2(\frac{9}{2})x+(\frac{9}{2})^2 =-72+(\frac{9}{2})^2[/tex]
[tex]x^2+2(\frac{9}{2})x+(\frac{81}{4}) =-7+(\frac{81}{4})[/tex]
[tex](x^2+(\frac{9}{2}))^2 =-7+\frac{81}{4}[/tex]
Therefore with the use of completing the square method [tex]81/4[/tex] should be added to solve the equation